Extremely high levels of multiple cytokines in the cord blood of neonates born to mothers with systemic autoimmune diseases. (March 2020) - Takahashi, Naoto; Nagamatsu, Takeshi; Fujii, Tatsuya; Takahashi, Kayo; Tsuchida, Yumi; Fujio, Keishi; Fujii, Tomoyuki
Highlights: Hypercytokinemia occurred in neonates born to mothers with autoimmune diseases. The hypercytokinemia was observed irrespective of their mothers' diseases. FGR and NRFS of unknown cause were all found in the hypercytokinemia group. The hypercytokinemia may have originated in neonatal immune tissues in utero. Abstract: Most infants born to mothers with autoimmune diseases are thought to be entirely healthy. However, the immunological conditions have not been examined thoroughly. Fourteen neonates born to mothers with systemic autoimmune diseases, namely systemic lupus erythematosus, mixed connective tissue disease, Sjögren's syndrome, rheumatoid arthritis, and systemic sclerosis, were included. Serum concentrations of 17 cytokines from the infants' umbilical artery (UA) and vein (UV) and from the mothers' peripheral blood were investigated by a bead array system. Cytokine expression in the placenta was investigated by immunohistochemical staining. The disease was controlled in all mothers, and none had chorioamnionitis. Hypercytokinemia was found in 11 neonates irrespective of their mothers' autoimmune diseases. In six neonates, serum cytokines were at extremely high levels. Four neonates were born by cesarean section because of a non-reassuring fetal status (NRFS) of unknown cause were all included in the hypercytokinemia group. However, all the subjects were discharged without any complications. The cytokine levels were almost the same between UA and UV, but the mothers' blood samples did not show elevation of serum cytokines. There were no differences in the expression of cytokines in the placenta among three patients with different serum cytokines levels. Hypercytokinemia frequently occurred and a cytokine storm state sometimes developed in neonates born to mothers with systemic autoimmune diseases. Growth restriction and NRFS may be related to hypercytokinemia in utero. It is plausible that the high level of cytokines in cord blood originate in neither the mother nor the placenta but in fetal immune tissues. It is important to investigate the immunological mechanisms, prevalence, and long-term influence of hypercytokinemia in a large sample size of neonates and mothers with systemic autoimmune diseases.